(untitled) (Journal of Hama University, 2025)
The research aimed to identify the degree of availability of critical thinking skills as well as the degree of availability of achievement motivation among fifth grade learners in Latakia City, in addition to studying the relationship between critical thinking skills and achievement motivation among the research sample of fifth grade learners in Latakia City. The research sample included (246) students, and the descriptive analytical approach was relied on. To achieve the purpose of the research, two tools were built, the first is the scale consisting of (30) phrases that measure their critical thinking, and a second achievement motivation scale, which consisted of (34) phrases that measure the degree of availability of achievement motivation among learners.The results of the research showed that the degree of availability of critical thinking skills among the learners of the fifth grade in Latakia City was high and that the degree of availability of achievement motivation among the research sample was high and there is a statistically significant and strong relationship between critical thinking skills and achievement motivation among a sample of fifth grade students in Latakia City, and the results also showed that there is no difference in the degree of availability of critical thinking skills according to the gender variable, and there is a difference in the degree of availability of achievement Motivation according to the gender variable in favor of females. Based on the results of the research, several proposals were made, the most important of which are: the need for basic education teachers to follow teaching methods and methods that raise students’ critical thinking skills, and the establishment of training courses on the skills necessary to enhance students’ motivation for academic achievement, and conducting other studies that study the relationship between critical thinking among students and motivation for academic achievement and other variables.